2021
DOI: 10.1007/s10570-021-04057-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-oxidized carboxycellulose nanofibers from moringa plant: effective bioadsorbent for mercury removal

Abstract: Mercury contamination in drinking water is a worldwide problem due to its severely harming effects on the human body. A nanostructured natural bioadsorbent, carboxycellulose nanofiber extracted from raw moringa plant using the nitro-oxidation method (termed NOCNF), capable of effectively remediating this problem has been demonstrated. Nitro-oxidation is a simple approach that can extract carboxylated nanocellulose directly from raw biomass. In this study, the produced NOCNF contained a large density of carboxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 47 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…100 Based on its abundant hydroxyl groups, cellulose can be chemically modified and crosslinked with other polymers. 101 Henriksson et al reported a new type of 3D scaffold composed of nanocellulose and hyaluronic acid with adipocytes. 102 After one week, the cell viability was still 95%.…”
Section: Part Ii: New Emerging 3d-printing Technologies Useful For Mi...mentioning
confidence: 99%
“…100 Based on its abundant hydroxyl groups, cellulose can be chemically modified and crosslinked with other polymers. 101 Henriksson et al reported a new type of 3D scaffold composed of nanocellulose and hyaluronic acid with adipocytes. 102 After one week, the cell viability was still 95%.…”
Section: Part Ii: New Emerging 3d-printing Technologies Useful For Mi...mentioning
confidence: 99%
“…Cellulose-based materials were reported for the adsorption of metal ions such as UO 2 2+ (Sharma et al, 2020a), As 3+ (Chen et al, 2019;Sharma S. K. et al, 2020), Cu 2+ (Qin et al, 2019), Cd 2+ (Movaghgharnezhad et al, 2020), Cr 6+ (Awang et al, 2019.;Reshmy et al, 2022), Pb 2+ (Hernández-Francisco et al, 2020;Sharma P. R. et al, 2021), and Hg 2+ (Chen et al, 2021). The functional groups of cellulose materials play an important role in the adsorption of metal ions.…”
Section: Adsorption Cellulose-based Adsorbents For Metal Ionsmentioning
confidence: 99%
“…In this regard, we aim to demonstrate that nanocellulose can be an effective coagulant/adsorbent to remove the Tl(I) contaminant from water [ 26 ]. In our previous study, we demonstrated that carboxylated cellulose nanofibers (CNFs) are generally effective for heavy metal ions removal [ 27 , 28 , 29 , 30 , 31 , 32 ]. Furthermore, anionic CNF can also be converted into cationic CNF through surface modification to remove metal ions in the anionic form.…”
Section: Introductionmentioning
confidence: 99%